1982
DOI: 10.1126/science.6800033
|View full text |Cite
|
Sign up to set email alerts
|

A 7-Hydroxymethyl Sulfate Ester as an Active Metabolite of 7,12-Dimethylbenz[ a ]anthracene

Abstract: 7-Hydroxymethyl-12-methylbenz[alpha]anthracene (7-HMBA), a carcinogenic major metabolite of 7,12-dimethylbenz[alpha]anthracene (DMBA) in liver, was transformed by liver cytosolic sulfotransferase to reactive 7-HMBA sulfate, which is mutagenic toward Salmonella typhimurium strain TA98. The mutagenicity of 7-HMBA in the presence of hepatic sulfotransferase was much higher than that of DMBA or 7-HMBA in the presence of hepatic monooxygenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(60 citation statements)
references
References 16 publications
0
60
0
Order By: Relevance
“…To our knowledge, benzylic alcohols are the only group for which a positive result has been obtained in a short-term test using an exogenous sulfate-conjugating system for the activation (5)(6)(7). In the present study, it was demonstrated that this effect involves a special mechanism, namely, substitution of the polar sulfate group by a nonpolar halogen group.…”
Section: Toxicological Implications Of Hampered Transport Of Active Smentioning
confidence: 70%
See 2 more Smart Citations
“…To our knowledge, benzylic alcohols are the only group for which a positive result has been obtained in a short-term test using an exogenous sulfate-conjugating system for the activation (5)(6)(7). In the present study, it was demonstrated that this effect involves a special mechanism, namely, substitution of the polar sulfate group by a nonpolar halogen group.…”
Section: Toxicological Implications Of Hampered Transport Of Active Smentioning
confidence: 70%
“…Strikingly, however, the addition of a sulfate-conjugating system usually decreased the mutagenicity of aromatic amines and their metabolites in Salmwnella typhimurium, whereas the covalent binding to isolated nucleic acids was enhanced (2)(3)(4). On the other hand, Watabe et al (5)(6)(7) have observed DNA binding as well as bacterial mutagenicity for benzylic sulfate esters and alcohols, the latter requiring the presence of a sulfotransferase-containing metabolic system. To study structural and metabolic parameters governing this mutagenicity, we have synthesized a series of benzylic alcohols and sulfate esters.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sulfonation is generally thought to be a detoxication process; however, the enzyme also activates certain promutagens, e.g. 5-methylchrysene (Blanchard et al, 2004), DMBA, cyclopenta [c,d,]pyrene and benzo [a]pyrene (Watabe et al, 1982;Surh et al, 1987Surh et al, , 1993Surh & Tannenbaum, 1995) by a mechanism that involves the conjugation of benzylic alcohols. Six cytosolic SULTs are known to be expressed in humans, including phenol SULTs, hydroxy SULTs and estrogen SULTs (Raftogianis et al, 1997;Daly, 2003;Moreno et al, 2005).…”
Section: (X) Epoxide Hydrolasementioning
confidence: 99%
“…SULT1A1 catalyze the sulfonation of N-hydroxy derivatives of arylamines and heterocyclic amines, which are presented in tobacco smoke, to form more reactive DNA-damaging electrophiles (Ozawa et al, 1994;Chou et al, 1995). Sulfonation can also activate another major class of tobacco carcinogens, polycyclic aromatic hydrocarbons (PAHs) and nitro PAHs (Watabe et al, 1982;Surh et Ozawa et al, 1998;Hirata et al, 2008). Among these, a common polymorphism (G638A) at codon 213 in exon 7 of SULT1A1 gene causes an Arg to His amino acid substitution.…”
Section: Introductionmentioning
confidence: 99%